Public and private goods in the development of additive manufacturing capacity. (9th June 2017) - Samford, Steven; Warrian, Peter; Goracinova, Elena
Abstract: The promotion of additive manufacturing (AM) as a set of enabling technologies has been a prominent feature of new policies seeking to revitalize manufacturing in developed economies. Because of its differences from traditional manufacturing technologies, small businesses, in particular, face high costs in adopting AM methods. How can governments assist small firms and their innovation ecosystems to make significant leaps in enabling technologies? This paper conceptualizes the challenges faced by groups of small enterprises adopting new technologies and a decentralized policy effort to systematically increase the use of advanced manufacturing technologies. In Canada, funding used by community colleges to create applied research centers has been intended to establish anchors for local "industrial commons" around advanced manufacturing methods. By providing both information and working capital to private sector partners, these community college programs should ideally mitigate challenges to the adoption of AM technologies—the so-called "valley of death"—in local ecosystems. There are many successful individual cases of partnership (i.e., private goods); however, this bottom-up approach seems to fail both as a means of promoting vibrant industrial commons (i.e., public goods) and as a coherent national strategy. We trace the challenges of this approach to principal-agent problems associated with layering new programs upon existing organizations, the density of program participants, and the presence of appropriate technologies.